2004
DOI: 10.1094/mpmi.2004.17.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The Phytoalexin-Inducible Multidrug Efflux Pump AcrAB Contributes to Virulence in the Fire Blight Pathogen, Erwinia amylovora

Abstract: The enterobacterium Erwinia amylovora causes fire blight on members of the family Rosaceae, with economic importance on apple and pear. During pathogenesis, the bacterium is exposed to a variety of plant-borne antimicrobial compounds. In plants of Rosaceae, many constitutively synthesized isoflavonoids affecting microorganisms were identified. Bacterial multidrug efflux transporters which mediate resistance toward structurally unrelated compounds might confer tolerance to these phytoalexins. To prove this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(161 citation statements)
references
References 65 publications
6
153
1
1
Order By: Relevance
“…Therefore, the TtgABC efflux pump may be a critical element in the competitive colonization of plant roots by P. putida, similarly to other MDR transporters found in soil-and plant-associated bacteria (28 -30). In addition, the fact that a mutant E. amylovora deficient in the MDR efflux pump AcrAB (60% identical to TtgAB) was impaired in its virulence against plants (27), emphasizes our hypothesis.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore, the TtgABC efflux pump may be a critical element in the competitive colonization of plant roots by P. putida, similarly to other MDR transporters found in soil-and plant-associated bacteria (28 -30). In addition, the fact that a mutant E. amylovora deficient in the MDR efflux pump AcrAB (60% identical to TtgAB) was impaired in its virulence against plants (27), emphasizes our hypothesis.…”
Section: Discussionmentioning
confidence: 62%
“…However, the particularly broad substrate specificity of this efflux system and the multidrug binding capacity of its cognate repressor TtgR raised the question concerning their physiological role(s). Based on the fact that the plant rhizosphere is one of the natural habitats of P. putida, and considering that the AcrB transporter from the plant pathogen Erwinia amylovora, involved in the resistance of this strain to various plant defense metabolites (27), is 60% identical to the TtgB transporter from P. putida DOT-T1E, we investigated the potential role of TtgABC in the resistance to plant-derived antimicrobials. To verify this hypothesis, the MICs of five plant secondary metabolites known to have antibacterial activities (45)(46)(47) were determined for both, P. putida DOT-T1E and its derivative mutant strain DOT-T1E18, deficient in the TtgABC efflux pump (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibiotic activity of their respective aglucones, phloretin and hydroquinone, against E. amylovora has long been demonstrated (Römmelt et al 2003b;Pontais et al 2008). Burse et al (2004) identified a multidrug efflux pump in E. amylovora, which confers resistance to apple phenolics like phloretin, naringenin, quercetin and catechin, contributing to bacterial virulence, which seems to confirm the role of phenolic compounds during the infection process (Pontais et al 2008). Phloretin was detected in all the hypanthium samples of various apple and pear cultivars, its levels in apple samples being approximately three times higher than in pear samples (Horváth et al 2004a).…”
Section: Hypanthium and Nectarymentioning
confidence: 99%
“…In E. coli, AcrAB-TolC mediate resistance toward metabolic byproducts such as bile salt, environmental antimicrobials, toxins, dyes, and detergents [5]. AcrAB-TolC of E. amylovora plays an important role in resistance toward phytoalexins, as virulence and fitness factors that are required for successful colonization of a host plant [6,7].…”
Section: Introductionmentioning
confidence: 99%